Cytotoxic, Anti-inflammatory, and Leishmanicidal Activities of Diterpenes Isolated from the Roots of Caesalpinia pulcherrima - Erharuyi, Osayemwenre; Adhikari, Achyut; Falodun, Abiodun; Jabeen, Almas; Imad, Rehan; Ammad, Muhammad; Choudhary, M. Iqbal; Gören, Nezhun (Planta Medica, 2017)
A phytochemical investigation on the chloroform extract of Caesalpinia pulcherrima roots led to the isolation of ten known furanocassane diterpenoids, vouacapen-5α-ol (1), 8,9,11,14-didehydrovouacapen-5α-ol (2), 6β-cinnamoyl-7β-hydroxyvouacapen-5α-ol (3), pulcherrin A (4), pulcherrin B (5), pulcherrin J (6), pulcherrimin A (7), pulcherrimin B (8), pulcherrimin C (9), and pulcherrimin E (10). Chemical transformation of 3 and 7 gave compounds 6β-hydroxyisovouacapenol C (11), 6β-cinnamoyl-7β-acetoxyvouacapen-5α-ol (12), and pulcherrimin D (13). Cytotoxicity of compounds 1-13 was evaluated against three cancer cell lines (MCF-7, HeLa, and PC-3). Anti-inflammatory potential of the compounds was evaluated via the oxidative burst assay using a luminol-amplified chemiluminescence technique. Leishmanicidal activity was tested against promastigotes of Leishmania major in vitro. Compounds 3, 4, 8, 9, and 10 were found active against all three cancer cell lines with IC50s ranging from 7.02 ± 0.31 to 36.49 ± 1.39 µM. Compounds 8 and 13 exhibited a potent inhibitory effect on reactive oxygen species generated from human whole blood phagocytes (IC50 = 15.30 ± 1.10 µM and 8.00 ± 0.80 µM, respectively). Compounds 3, 9, and 13 showed significant activity against promastigotes of L. major (IC50 = 65.30 ± 3.20, 58.70 ± 2.80, and 55.90 ± 2.40 µM, respectively).
Keywords: Caesalpinia pulcherrima; Caesalpiniaceae; cassane diterpenoids; cytotoxicity; cancer cells; leishmanicidal activity; anti-inflammatory activity